2021
DOI: 10.1186/s13071-021-05103-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyathostomin resistance to moxidectin and combinations of anthelmintics in Australian horses

Abstract: Background Cyathostomins are the most important and common parasitic nematodes of horses, with > 50 species known to occur worldwide. The frequent and indiscriminate use of anthelmintics has resulted in the development of anthelmintic resistance (AR) in horse nematodes. In this study we assessed the efficacy of commonly used anthelmintics against cyathostomins in Australian thoroughbred horses. Methods Two drug efficacy trials per farm were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
(50 reference statements)
2
16
0
2
Order By: Relevance
“…A subsequent study documented ivermectin resistance in a group of US born yearlings raised on a different farm in the same area ( Nielsen et al, 2022a ), demonstrating that macrocyclic lactone resistance is established in the domestic US equine population as well. Furthermore, moxidectin resistance was recently demonstrated in groups of weanlings and yearlings in Australia ( Abbas et al, 2021 ). Taken together, these recent data suggest that a long-awaited breakthrough of macrocyclic lactone resistance in equine strongylids has finally happened, and that many more reports can be expected in coming years.…”
Section: Cyathostominsmentioning
confidence: 97%
See 1 more Smart Citation
“…A subsequent study documented ivermectin resistance in a group of US born yearlings raised on a different farm in the same area ( Nielsen et al, 2022a ), demonstrating that macrocyclic lactone resistance is established in the domestic US equine population as well. Furthermore, moxidectin resistance was recently demonstrated in groups of weanlings and yearlings in Australia ( Abbas et al, 2021 ). Taken together, these recent data suggest that a long-awaited breakthrough of macrocyclic lactone resistance in equine strongylids has finally happened, and that many more reports can be expected in coming years.…”
Section: Cyathostominsmentioning
confidence: 97%
“…Thus, X means that resistance was tested, but not found, and X-AR means that resistance was tested and found. Country Publication Benzimidazoles Pyrimidines Macrocyclic lactones Algeria Boulkaboul et al (2006) X-AR X Australia Pook et al (2002) X-AR X-AR X Abbas et al (2021) X-AR X-AR Belgium Dorny et al (2000) X-AR X-AR Brazil Toscan et al (2012) X-AR Canever et al (2013) X-AR X-AR X-AR Felippelli et al (2015) X-AR Saes et al (2016) X-AR X Vera et al (2020) X-AR X Flores et al (2020) X-AR X-AR X-AR Martins et al (2021) X-AR X-AR Lignon et al (2021) <...…”
Section: Cyathostominsmentioning
confidence: 99%
“…Resistance to benzimidazoles and pyrantel is known to be widespread in strongyle nematodes of horses (Raza et al 2019 ; Dauparaitė et al 2021 ; Matthews 2014 ; Rendle et al 2021 ; Coles et al 2006 ; von Samson-Himmelstjerna 2012 ; Kenealy 2019 ; Stratford et al 2011 ; Tzelos and Matthews 2016 ; Tzelos et al 2019 ; Kaplan and Vidyashankar 2012 ) and has also been reported from Germany (Traversa et al 2009b ; Wirtherle et al 2004 ). In comparison, there are only a few reports of resistance to ivermectin in strongyles (Traversa et al 2009a ; Relf et al 2014 ; Geurden et al 2013 ; Kaplan et al 2004 ; Johnson and Biddle 2021 ) and moxidectin (Abbas et al 2021 ; Tzelos et al 2017 ; Nielsen et al 2020 ; Johnson and Biddle 2021 ), none of them from Germany. More often than clear resistance, longer egg reappearance periods have been reported for many regions of the world (Daniels and Proudman 2016 ; Tzelos et al 2017 ; Johnson and Biddle 2021 ) including Germany (von Samson-Himmelstjerna et al 2007 ); and this is considered to be a hint of a developing anthelmintic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Brandenburg, from where the majority of samples in this study came, no hints for resistance or a prolonged egg reappearance period were observed in 2007 (Fischer et al 2015 ). The fact that moxidectin treatment is associated with the longest egg reappearance period among all licenced equine anthelmintics (Relf et al 2014 ; Traversa et al 2009b ; Schumacher and Taintor 2008 ; Johnson and Biddle 2021 ) and that an increased egg reappearance period (Relf et al 2014 ; Traversa et al 2009b ; Schumacher and Taintor 2008 ; Johnson and Biddle 2021 ) or even resistance (Abbas et al 2021 ) were only rarely reported for moxidectin is the most likely explanation for the stronger or longer lasting protective effect of moxidectin in comparison to other anthelmintics in the present study. In contrast to moxidectin, ivermectin and fenbendazole treatments were only associated with significantly lower strongyle egg-shedding data than pyrantel in the bivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Auf dem letzten Weltkongress für Veterinärparasitologie (WAAVP) wurde nun der erste Fall einer aus Irland eingeschleppten Resistenz der kleinen Strongyliden gegen ML in Kentucky (USA) vorgestellt 1 . Mittlerweile wurden auch ML-Resistenzen in Kanada und Australien beschrieben 2 , 3 . Über die Situation in Mitteleuropa ist wenig bekannt, weil aktuelle flächendeckende Wirksamkeitsstudien fehlen.…”
Section: Introductionunclassified